Bedside measurement of microcirculation in critically ill patients: A scoping review protocol - Sogand Sarmadi; Neda Sanaie; Fateme Monjazebi; Akbar Zare-Kaseb (PLoS ONE, 2026)
Background Microcirculatory dysfunction is a pivotal factor in the pathophysiology and prognosis of critically ill patients. While traditional resuscitation primarily emphasizes macrocirculatory parameters such as mean arterial pressure (MAP), emerging evidence indicates that maintaining a normal MAP alone does not guarantee adequate microvascular perfusion. As a result, bedside evaluation of microcirculation has garnered increased interest as a supplementary method to hemodynamic monitoring. Objective This scoping review aims to systematically map and categorize existing bedside tools and technologies used to assess microcirculation in critically ill patients. The review will summarize their clinical applications, advantages, limitations, and integration into intensive care practice, and identify key evidence gaps to guide future research. Methods In accordance with the Joanna Briggs Institute (JBI) framework and the PRISMA-ScR guidelines, a comprehensive literature search will be conducted across MEDLINE, Scopus, Web of Science, Embase, CINAHL, the Cochrane Library, and ProQuest. Additionally, the grey literature search will be complemented by searches of trial registries such as ClinicalTrials.gov and the WHO ICTRP. Eligible studies will encompass all primary research involving critically ill patients evaluated for microcirculatory function at the bedside within intensive care units (ICUs). Data extraction and synthesis will adhere to an inductive–deductive thematic approach based on Braun and Clarke’s methodology, complemented by the PAGER framework to identify patterns, advances, gaps, and evidence pertinent to clinical practice. Conclusion By mapping the landscape of bedside microcirculatory assessment tools, this review will support the translation of microcirculatory monitoring from research to clinical practice, thereby promoting physiologically guided, individualized management in critically ill patients. Registration This protocol is prospectively registered in OSF.io.